Diplomasi Publik Pemerintah Provinsi Jawa Timur melalui East Java Fashion Harmony Tahun 2022-2024 - Fajarianti, Lintang; Setiawan, Siti Anggraini; Sonata, Risha Dygta; Utomo, Ario Bimo (Journal of Integrative International Relations, 2025)
This Study is an analysis about the public diplomacy conducted by the East Java Provincial Government through East java Fashion harmony (EJFH) in 2022-2024. EJFH is an annual fashion agenda designed to promote the archipelago’s at the international level. EJFH can also be implemented through international cooperation with Australia. This study uses descriptive qualitative methods with data obtained through news articles, direct interviews with the marketing staff of the East Java Department of Culture and Tourism, as well as academic literature related to public diplomacy. In this study, qualitative data analysis was used and presented in the form of a narrative. The result of this study shows that EJFH succeeded in presenting East Java's culture through public diplomacy. The implementation of EJFH not only introduces Indonesian culture but also strengthens Indonesia’s image through cultural introduction and cross-country collaboration. This study emphasizes the importance of introducing local culture through public diplomacy and also supports the strengthening of international cooperation.